Microscopic mechanism study of the creep properties of soil based on the energy scale method - Yuan, Jie; Wang, Tao Jin; Chen, Jian; Huang, jian An (Frontiers in Materials, 2023)
The study of rheological properties of soils is of great importance for the later settlement and safe use of buildings (structures). The mineral composition of soil, mineral content and the amount of bound water of particles have obvious effects on the rheological properties of soil. In this paper, analyzing the relationship between mineral composition, mineral content, water binding and other factors on the coefficient of viscosity of soil during rheology through direct shear creep test. Then, the influence of the bound water state on the particle surface on the contact properties of particles during soil rheology is investigated at the microscopic level, and based on this, an energy scale method is established that can measure the microscopic state of the above three factors as well as the macroscopic soil rheological phenomena. The results show that this method can reveal the intrinsic mechanism of soil rheology at the microscopic level and can quantitatively measure the effect of soil factors on soil rheological properties.